Life cycle assessment of recycled aggregates applied to cement-based construction materials - Bello, Lukas Bruno Damazio; Calmon, João Luiz (Brazilian Journal of Production Engineering, 2024)
Recycled Aggregates (RA) emerge as a solution to reduce environmental impacts by converting Construction and Demolition Waste (CDW) into construction material. The general objective of the research is to carry out a Life Cycle Assessment (LCA) of the use of RA for the production of cement-based construction materials, aiming to evaluate the influence of RA on environmental impact indicators. In total, 24 traits were used for the use of RA; in mortars, prefabricated blocks, non-structural, structural and self-compacting concrete. The OpenLCA program was used to calculate environmental impacts using 5 different impact methods. When analyzing the Life Cycle Inventory and interpreting the LCA results, it is noted that the production of RA presents itself as an environmentally viable solution in relation to the reference material as long as the impacts avoided by recycling are accounted for. CDW transport is mainly responsible for the impacts generated. The recycled material proved to be environmentally viable at various replacement levels, achieving reductions of up to 43.6% in indicators. RA has the potential to replace Natural Aggregates (NA) in almost all scenarios analyzed.